Situação do aleitamento materno entre policiais militares da região metropolitana de Belo Horizonte e fatores associados ao desmame - Tatiana Caroline Santiago Bossert Freitas (2012)
Breastfeeding satisfies the nutritional needs and is responsible for better child development, especially in the first two years of life. However, rarely children are breastfed until this period is considered ideal. In this context, it is necessary to carry out research to identify factors associated with length of breastfeeding. The use of drugs is one of the factors identified as responsible for the reduced duration of breastfeeding, there is a lack of studies on the safety of using medications to the fetus and infant. This study evaluated the breastfeeding status, factors associated with weaning and duration of exclusive breastfeeding and investigated the association of medication use with duration of breastfeeding during pregnancy and lactation in mothers with children of military personnel up to 24 months in metropolitan region of Belo Horizonte. It is cross-sectional study with 100 mothers who had children in the military from May 2007 to September 2011, held in the units of the Military Police of Minas Gerais. The data collected were: frequency of breastfeeding, socioeconomic, military, health care and maternal and childhealth habits. The analysis of association between weaning, exclusive breastfeeding and the study variables in the univariate analysis were performed. The variables that were significant at the 0.20 level were candidates for the multivariate model. The Mann- Whitney test and t test were used to verify the time of exclusive breastfeeding andbreastfeeding. The publication of the Food and Drug Administration (1980) was adopted for safety analysis of drug use during pregnancy, and publications of the American Academy of Pediatrics (2001) and Hale (2006) were chosen to evaluate the safety of using medication during breastfeeding. Breastfeeding occurred in 94% of cases and their medianduration was 7.2 months. Exclusive breastfeeding was practiced by 23% of mothers and their median duration was four months. There was no significant difference in duration of breastfeeding among mothers. according to military rank, educational level and operationalactivities. Multivariate analysis showed a positive association between weaning and the following variables: mother's marital status (married), information on the importance of breastfeeding during prenatal care and use of non-human milk. The variable that was positively related to longer duration of exclusive breastfeeding was: mothers with two children prior. The frequency of drug use was 76% during pregnancy and lactation 47%.The use of medication during pregnancy and lactation was not associated with duration of breastfeeding. It was concluded that the operational activity did not interfere in the prevalence of breastfeeding among mothers military. The use of drugs appeared as a frequent practice during pregnancy and breastfeeding. The frequent use of safe drugs contributed to the use of drugs does not associate the duration of breastfeeding. Action planning can intervene on factors related to health care and maternal and child health habits in order to improve the content of breastfeeding.